Pengaruh Leverage, Profitabilitas, Ukuran Perusahaan, Kompleksitas Operasi Perusahaan, dan Reputasi Auditor terhadap Audit Delay - Christiane, Grace Sabrina; Indrabudiman, Amir; Handayani, Wuri Septi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This research aims to test and analyze empirically the influence of leverage, profitability, company size, complexity of company operations, and the reputation of auditors against audit delays. Methodology/approach: A manufacturing firm in the food and beverage subsector that is listed on the Indonesia Stock Exchange for the years 2016 to 2020 constitutes the study’s population. 18 companies were chosen as samples using the purposive sampling technique. The data are examined using many linear regressions. Results/findings: The results showed that (1) the profitability and reputation of the auditor have a negative and significant effect on audit delay, (2) leverage, firm size, and the complexity of the company’s operations have no effect on audit delay Limitations: The limitation of this study lies in the sample selection technique used, namely purposive sampling where the sample selection criteria have been determined previously. Thus, the sample of this study does not guarantee representation of the study population. Contribution: This study contributes empirical evidence that can be used by auditors to study the factors that can affect audit delay.